IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Utia, Meilan; Mas, Sitti Roskina; Suking, Arifin (Equity In Education Journal, 2024)
This study aims to describe the implementation of the Merdeka Curriculum in enhancing students' independent learning, focusing on: (1) teachers' strategies to improve students' independent learning, (2) strategies for the sustainability of independent learning programs, and (3) the evaluation of students' independent learning based on the implementation of the Merdeka Curriculum. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic analysis. Data validation was conducted through triangulation of sources and methods. The results show that the implementation of the Merdeka Curriculum at SDN 22 Dungingi has successfully enhanced students' independent learning through interactive learning supported by technological tools such as Chromebooks and internet connectivity provided by the Smart Learning Community (KOMBEL). Chromebooks enable students to independently access digital educational resources, improve their digital literacy, and develop lifelong learning skills. Additionally, formative and summative evaluations conducted by teachers help students identify their strengths and weaknesses, foster self-reflection, and increase responsibility for their learning processes.